Investigating the Meaning of Nurun Ala Nurin “A Study of Falsafi Tafsir on Divine Light in Qur'an” - Didi Darmadi; Sudjiat Zubaidi; Muhammad Zhilal (al-Afkar, Journal For Islamic Studies, 2026)
The phrase “Nurun ala Nurin" (نورٌ على نور) from Surah An-Nur (24:35) in the Qur'an is often interpreted as a symbol of spiritual enlightenment within Islamic tradition. The literal meaning of this phrase is "Light upon Light," which points to a deeper understanding of the concept of light in the metaphysical context of Islam. The study Exploring the Meaning of Nurun Ala Nurin: A Philosophical Exegesis on Divine Light in the Qur'an, employs a qualitative approach using literature review methodology. This research analyzes data from both classical and contemporary tafsir (Qur'anic exegesis), utilizing comparative and interpretative methods to uncover a deeper understanding of the concept of “Nurun ala Nurin" within Islamic thought. The study concludes that, firstly, the philosophical interpretation of “Nurun ala Nurin" reveals that the light not only refers to intellectual enlightenment but also to inner illumination that leads to closeness to God and a higher level of understanding. Secondly, while classical and contemporary tafsirs adopt different approaches, both agree that “Nurun ala Nurin " refers to the divine guidance granted to the believers.